Marketing research of the electric power market in Yaroslavl region - N. G. Lyubimova; A. D. Lebedeva; A. S. Flaxman (Вестник университета)
The article contains a marketing study of the electricity market in Yaroslavl region, including analysis of electricity consumption and tariff policy. The purposes of the work are to forecast the electricity consumption in the region, and to assess the dynamics and structure of electricity tariffs for various categories of consumers. When forecasting the electricity consumption, various macroeconomic and statistical methods have been used, including extrapolation methods; when assessing the tariff policy, general scientific methods of analysing the dynamics and structure of indicators have been applied. The results obtained prove the growing need of the region for electricity: an increase of about 2% per year until 2030. The growth of margin al unregulated prices (tariffs) for the electricity (capacity) for other consumers is below the inflation rate, with the exception of 2023, when a trend towards a decrease in cross-subsidisation of the population by other consumers emerged. Also, the electricity tariffs (capacity) for the population and equivalent categories of consumers in crease. They are below the rate of wage growth, but above the rate of inflation both in general for the period and in individual years. The share of household expenses on the electricity is less than 1%, which makes it possible to increase the electricity tariffs for the population while reducing the cross-subsidisation. The obtained   data are applicable in socio-economic monitoring to assess the burden on businesses and population, and to forecast the consequences of the tariff policy. The prospects of the study are associated with an in-depth analysis of the impact of external factors (sanctions, technological changes) on the energy market.